A Theory of Optimal Green Defaults - Georg Meran; Reimund Schwarze (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper develops an analytical framework for studying the Baumol-Oates efficiency of traditional single instrument abatement policies vis-a-vis green defaults in the face of price inertia and deliberate defaulting of subpopulations. In this special case of behavioural heterogeneity command and control approaches can outperform price-based instruments and pure tax/subsidy schemes need to be adjusted in order to achieve politically desired levels of abatement. Moreover we prove that choice-preserving nudges are superior to any single-instrument policy in this case. An average marginal abatement cost rule is developed to optimise the green defaults and traditional policies of standards and prices under different degrees of market rigidity.
Keywords: H23; Q58; L51; 330